Regional- and local-scale variations in benthic megafaunal composition at the Arctic deep-sea observatory HAUSGARTEN. (February 2016) - Taylor, J.; Krumpen, T.; Soltwedel, T.; Gutt, J.; Bergmann, M.
Abstract: The Long-Term Ecological Research (LTER) observatory HAUSGARTEN, in the eastern Fram Strait, provides us the valuable ability to study the composition of benthic megafaunal communities through the analysis of seafloor photographs. This, in combination with extensive sampling campaigns, which have yielded a unique data set on faunal, bacterial, biogeochemical and geological properties, as well as on hydrography and sedimentation patterns, allows us to address the question of why variations in megafaunal community structure and species distribution exist within regional (60–110 km) and local (<4 km) scales. Here, we present first results from the latitudinal HAUSGARTEN gradient, consisting of three different stations (N3, HG-IV, S3) between 78°30′N and 79°45′N (2351–2788 m depth), obtained via the analysis of images acquired by a towed camera (OFOS-Ocean Floor Observation System) in 2011. We assess variability in megafaunal densities, species composition and diversity as well as biotic and biogenic habitat features, which may cause the patterns observed. While there were significant regional-scale differences in megafaunal composition and densities between the stations (N3=26.74±0.63; HG-IV=11.21±0.25; S3=18.34±0.39 individuals m −2 ), significant local differences were only found at HG-IV. Regional-scale variations may be due to the significant differences in ice coverage at each station as well as the different quantities of protein available, whereas local-scale differences at HG-IV may be a result of variation in bottom topography or factors not yet identified. Highlights: We study community composition and diversity at local- and regional-spatial scales. Analysis of 3 stations along latitudinal gradient obtained via towed camera images. Megafaunal densities and composition vary along latitudinal gradient. Significant differences in sea–ice and sediment protein key between sites. Low local-scale variation observed, slope effects potentially most important.